Prevalence and Factors Associated with the Depressive and Anxiety Symptoms Amongst Antenatal Women - S.R.M, Arifin; A.S., Ismail; S., Samsudin; N.A., Hassan; W.H., Wan Mamat (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: There is a wide range of antenatal mental disorder prevalence, including depression, anxiety and worry across countries. Studies to determine the association between sociodemographic factors, social support and antenatal mental health disorders have since produced inconsistent results. The aim of this study was to determine the prevalence and factors associated with antenatal anxiety, worry and depression among pregnant women. MATERIALS AND METHODS: A total of 262 women who attended the antenatal clinic at any of the four. Mother and Child Health clinics in Kuantan, Pahang participated in this cross-sectional study. The social support, depression, anxiety and worry were measured using the Multidimensional Scale of Perceived Social Support (MSPSS), the Edinburgh Postnatal Depression Scale (EPDS), State-trait Anxiety Inventory (STAI) and Cambridge Worry Scale (CWS), respectively. RESULTS: Of these women, 20.2% had depressive symptoms, 22.5% had antenatal anxiety, and 79% had antenatal anxiety. Women with lower education background were at risk of antenatal depression whereas working and first-time mothers were at risk of experiencing worry in pregnancy. This study has proven that social support plays a significant role in alleviating worry during pregnancy. CONCLUSION: Considering that the high level of worry in pregnancy could result in negative pregnancy outcomes and postnatal depression, there should be a screening tool used to measure psychological wellbeing of the pregnant mother within the clinical practice. The element of social support should be included in the intervention targeting women with lower educational level, primiparous and working mothers.